Are parents of intellectually gifted child(ren) at higher, lower or equal risk for parental burnout? - Saliez, Zoé; Vandeuren, Anthony; Roskam, Isabelle; Mikolajczak, Moïra (Frontiers in Psychiatry, 2022)
Being a parent can lead to exhaustion when risk factors offset protective factors. Recent research enabled the understanding of parental burnout antecedents among parents of typical and atypical children, but we know few about parental burnout (PB) among parents of intellectually gifted (IG) children. At the same time, several qualitative studies report particularities of being a parent of IG child(ren). In this quantitative study, we explore whether the risk of PB is different for parents of IG child(ren) than for the global population. We use two samples of 196 strictly matched parents: the first is composed of parents having at least one IG child, the second is constituted of demographically matched control parents (data collection took place from November 2019 to February 2020). We use Kruskal-Wallis analysis to compare groups. The results suggest that having an IG child does not significantly modify the risk of PB (Mean IG group = 32.45, SD = 28.21; Mean control group = 27.69, SD = 25.58; KW = 3.500, p = .06; Cohen’s d = .18). Implications and future perspectives are discussed, including the relevance of taking into account other special features of the IG child and the intellectual giftedness of the parent in future researches.